Chess For Children - Nottingham, Ted; Wade, Bob; Lawrence, Al (Sterling Publishing Co., Inc. New York, 1993)
Uses the revolutionary Lincolnshire system to explain how to play, enjoy, and master chess and recounts anecdotes about notable players in the history of the game.
Inculdes index
Keywords: Chess -- Juvenile Literature